Impact of freeze-drying and subsequent storage on milk metabolites based on 1H NMR and UHPLC-QToF/MS. (October 2020) - Zhu, Dan; Kebede, Biniam; Chen, Gang; McComb, Kiri; Frew, Russell
Abstract: This study is the first to investigate the effect of freeze-drying on raw milk metabolites using untargeted metabolomics. To detect as many metabolites as possible in the liquid fractions, a multiplatform metabolomics approach was implemented using both NMR and MS-based techniques. The chemical fingerprint of freeze-dried milk powder was monitored during storage at three temperatures (room temperature, 4 °C, −20 °C) for up to 224 days. This study demonstrated that freeze-drying was an efficient means of drying milk resulting in only minor changes to the metabolites. With respect to storage, freeze-dried milk powders stored at 4 °C and −20 °C exhibited a stable metabolome while samples stored at 20 °C resulted in a clear change. During ambient storage, the concentrations of orotic acid, riboflavin and acetyl-carbohydrate reduced while those of fatty acids, threonic acid and uridine increased. The results from this study provide the foundation for experiment design and marker selection for further studies on milk metabolomics. Highlights: Freeze-drying and storage effect on raw milk was studied by untargeted metabolome. Freeze-drying resulted in only minor changes to the raw milk metabolites. Freeze-dried milk powders stored at 4 °C and −20 °C exhibited a stable metabolome. Freeze-dried milk powders stored at room temperature resulted in a clear change.